The dynamic load on hamstring muscles during sprinting - Liu, Y.; Wei, S.; Sun, Y.; Zhong, Y. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to analyze the load condition on hamstring muscles during stance and swing phase of sprinting. Three-dimensional videographic and ground reaction force data were collected and the intersegmental dynamics of lower limb was quantified while eight elite male sprint runners performed sprint running with maximum effort. During initial stance phase, the ground reaction torque (EXT) was the main passive torque at knee and hip. During late swing phase, it was motion-dependent torque (MDT) as well. The muscle torques counteracted the large effect of EXT and MDT. This result revealed that the hamstring muscles would suffer from tremendous loads in both initial stance phase and late swing phase. Thus it can be speculated that hamstring muscles were exposed to a higher risk of injury during these two phases in sprinting.